Ethnic-racial relationships in theater teacher training - Monique Priscila de Abreu Reis; Tatiane Cosentino Rodrigues (Universidade Federal de Santa Catarina, 2019)
With reference to Law 10.639/2003, it was aimed to understand how future theatrical teachers are being trained to education for ethnic-racial relations. Considering the area of art as a priority in the implementation of ethnic-racial themes in Basic Education - as set out in the Curriculum Guidelines for Teaching Afro-Brazilian and African History and Culture and for Education of Ethnic-Racial Relations - and identifying a theoretical gap in which specifically concerns the training of theater teachers in the theme in question, it was sought the elaboration, based on interviews with researchers in the area, of possible content proposals, approaches and methodologies of initial training for teachers / the theater in the perspective of education for ethnic-racial relations and the teaching of Afro-Brazilian and African History and Culture. As a result, we bring to the debate formative possibilities centered on an approximation between university and community contemplating activities of research and extension, new epistemologies and different ways of conceiving and performing theatrical performance.